AI for Not Bad - Moore, Jared (Frontiers in Big Data, 2019)
Hype surrounds the promotions, aspirations, and notions of ‘artificial intelligence (AI) for social good’ and its related permutations. These terms, as used in data science and particularly in public discourse, are vague. Far from being irrelevant to data scientists or practitioners of AI, the terms create the public notion of the systems built. Through a critical reflection, I explore how notions of AI for social good are vague, offer insufficient criteria for judgement, and elide the externalities and structural interdependence of AI systems. Instead, the field known as ‘AI for social good’ is best understood and referred to as ‘AI for not bad.’